Spatio-temporal changes of littoral macrophytes along hydrological conditions in Yliki, a Greek lake - Mavromati, E.; Giourieva, V.; Papadimos, D.; Apostolakis, Antonis; V. Tsiaoussi (2025)
p. 641-642 In: Proceedings of the 13th World Congress of EWRA on Water Resources and Environment, Palermo, Italy 24 - 28 2025.